2022
DOI: 10.21203/rs.3.rs-2033136/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of Selenohomolanthionine supplementation on the rumen Eukaryotic Diversity of Shaanbei white cashmere wether goats

Abstract: Selenium (Se) is an important microelement for animal health. However, the knowledge about the effects of Se supplementation on rumen eukaryotic community remains less explored. In this study, the ruminal eukaryotic diversity in Shaanbei white cashmere goats fed a basal diet (0.016 mg/kg Se, control group [CG]) were compared to those animals given basal diet supplemented with different levels of organic Se in the form of Selenohomolanthionine (SeHLan), namely low Se group (LSE, 0.3 mg/kg), medium Se group (MSE… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…An in vitro study showed that biotin was important in maintaining the viability of isolated sheer secondary hair follicles [5], where supplementation increased the proportion of follicles continuing to grow and biotin deficiency reduced the proliferation of basal keratinocytes [8]. A study from our group showed that supplementation of 10 mg/d rumenprotected biotin (RPB) per goat increased the cashmere growth rate during the cashmere fiber growing period [9]. These results demonstrated potential benefits of biotin and indicated that it may be more pronounced in cashmere goats.…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study showed that biotin was important in maintaining the viability of isolated sheer secondary hair follicles [5], where supplementation increased the proportion of follicles continuing to grow and biotin deficiency reduced the proliferation of basal keratinocytes [8]. A study from our group showed that supplementation of 10 mg/d rumenprotected biotin (RPB) per goat increased the cashmere growth rate during the cashmere fiber growing period [9]. These results demonstrated potential benefits of biotin and indicated that it may be more pronounced in cashmere goats.…”
Section: Introductionmentioning
confidence: 99%